1970
DOI: 10.3329/jbsp.v4i1.4062
|View full text |Cite
|
Sign up to set email alerts
|

Allergen Skin Test Reactivity and Serum Total IgE Level in Adult Bronchial Asthmatic Patients

Abstract: Background : Asthma affects more than 100 million people worldwide. Increased morbidity is multifactorial and may include increased exposure to indoor allergens and environmental pollutants, overuse of beta-2 agonist, underuse of anti-inflammatory mediators and limited education about health care. Allergy represents a specific alteration in biologic reactivity mediated by an immunologic mechanism and resulting in an adverse physiologic response. Objective : Some of the type of allergen's sensitivity by skin pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Inconsistent result reported in Adult Bronchial Asthmatic Patients by Parveen etal (20) in Pakistan , and children with respiratory allergy in Iran (21) , as both studies find the association between the positive skin prick test and elevated serum total IgE were not statistically significant (P >0.05).…”
Section: Discussionmentioning
confidence: 85%
“…Inconsistent result reported in Adult Bronchial Asthmatic Patients by Parveen etal (20) in Pakistan , and children with respiratory allergy in Iran (21) , as both studies find the association between the positive skin prick test and elevated serum total IgE were not statistically significant (P >0.05).…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies demonstrated that, the number of eosinophils is increased in blood and tissue in patients with atopic diseases [9,10]. Many investigators used total IgE and eosinophil count for evaluating allergic diseases [11,12,13]. The aim of this study is to investigate the role T-IgE level and Eosinphil count in patients with allergic asthma; allergic rhinitis and allergic urticaria compared to the healthy control.…”
Section: Introductionmentioning
confidence: 97%